Predicting a contact's sensitivity to initial conditions using metrics of frictional coupling. (April 2017) - Flicek, R.C.; Brake, M.R.W.; Hills, D.A.
Abstract: This paper examines two metrics of frictional coupling, which are then used to predict how sensitive a frictional contact's steady-state behavior is to its initial conditions. Based on a large set of numerical simulations with different contact geometries, material combinations, and friction coefficients, a contact's sensitivity to initial conditions is found to be correlated with the product of the coupling metric and the friction coefficient. For cyclic shear loading, this correlation is maintained for simulations with different contact geometries, material combinations, and friction coefficients. However, for cyclic bulk loading, the correlation is only maintained when the contact edge angle is held constant. Abstract : Highlights: Presents two computationally efficient metrics of frictional coupling that predict how sensitive frictional contacts are to their initial conditions. Presents a wide array of numerical results showing that the product of the coupling metric and the friction coefficient predict a contact's sensitivity to initial conditions. For bulk-loaded contacts, the steady-state response is sensitive to the contact edge angle, whereas for shear-loaded contacts, it is very insensitive to edge angle.